2022
DOI: 10.1039/d1cp05900a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the wetting discrepancy in calcium alumino silicate hydrate induced by Al/Si ratio

Abstract: Changes in the wettability of CASH with different Al/Si ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Zhou et al studied the effect of PVA fiber modification on the interface properties and revealed the interaction mechanism between the modified PVA fiber/nanosilica coating and the cementitious phase interface. In addition, molecular dynamics can reveal the microscopic physical and chemical processes and mechanisms of concrete under macroscopic phenomena such as erosion resistance, , elastic properties, fluidity, wettability, , fracture toughness, etc., thus comprehensively understanding the structural properties and mechanical behavior of building materials and providing a strong guarantee for the prediction and modification of new materials.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al studied the effect of PVA fiber modification on the interface properties and revealed the interaction mechanism between the modified PVA fiber/nanosilica coating and the cementitious phase interface. In addition, molecular dynamics can reveal the microscopic physical and chemical processes and mechanisms of concrete under macroscopic phenomena such as erosion resistance, , elastic properties, fluidity, wettability, , fracture toughness, etc., thus comprehensively understanding the structural properties and mechanical behavior of building materials and providing a strong guarantee for the prediction and modification of new materials.…”
Section: Introductionmentioning
confidence: 99%
“…(a), acute and obtuse angles of the dipole angle correspond to the water molecule's O-H bonds pointing away from and towards the substrate, respectively. Layering the calculation of the dipole angle of water molecules51,52 facilitates a deeper understanding of the orientational changes resulting from the varying distances between water molecules in the unfrozen water film and both the substrate and the ice crystal. Considering the different interface conditions on both sides of the unfrozen water film and the relatively thin thickness of the water film, we analyzed the dipole angle of water molecules at the CSH-water interface (À1 Å to 1 Å), an inner layer within the unfrozen water film (1 Å to 3 Å), and the icewater interface (within a range of AE1 Å from the ice crystal surface).…”
mentioning
confidence: 99%